Mind Your Gap between Entry English Proficiency and Graduation Expectation - Uraiwan Sae-Ong; Shaik Abdul Malik Mohamed Ismail (Asian TESOL Journal, 2021)
In recent years, the trend of teaching and learning English as a foreign language in Thai universities have changed drastically. This can be seen by the changes in the English as a foreign language curriculum and the manner it is being taught in schools as well as in the universities. The main objective of these changes is to prepare students to participate more aggressively in the ASEAN community, where English is the universal language. Thai universities launched a new policy about English graduation requirements aligned with the Common European Framework of Reference (CEFR). One area of interest is whether there is a gap between the entry English proficiency and English graduation expectation. Thus, this study sought to gauge the gap between English oral proficiency among the Thai 1st year undergraduates and the expected exit proficiency level (B2 CEFR). Results suggest that almost all 1st-year university students in Thailand have a tremendous gap between the real entry English oral proficiency level and the high expectations exit proficiency level. This information about the gap would allow the universities to prepare their students accordingly.